Building Resilience in Education for Academic Continuity During Disruption - Folashade Afolabi; Oluwafemi Abayomi Olajuyigbe (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2023)
The traditional method of learning prevailed in the educational system up until the outbreak of the COVID-19 pandemic, which brought a turning point by digitalising learning. Education shifted from traditionally student-centred to digital learning. The transition made learning difficult and students did not cope easily with the new trend. This study investigated learners’ experience of the paradigm shift to digital learning under three stages: Anticipation, Coping, and Adaptation. Two hundred and ten (210) senior secondary school 2 students in the Eti-Osa Local Government Area of Lagos State were purposively selected. A 21-item online questionnaire with a 4-point Likert scale was used for data collection. The instrument was validated and the reliability was confirmed using Cronbach’s alpha (0.78). The data were analysed using descriptive statistics. From the results, the participants were able to identify the various challenges encountered during the transition and discover how institutions can be resilient during disruption.